Proyek Intervensi Organisasi - Siti Nuraini; Firmansyah Putra Ramadhan; Ansori Ansori (CV. ITTC INDONESIA, 2026)
An organizational intervention project is a planned change strategy aimed at increasing organizational effectiveness through improvements to its structure, systems, and work culture. This study aims to analyze the synchronization between organizational development theory and its implementation in a case study of an educational institution. The method used is a descriptive qualitative approach using literature review and case study analysis techniques. Data were obtained from Indonesian journals and books from the past ten years that discuss organizational development, technostructural interventions, and change communication. The results indicate that interventions initiated with a comprehensive organizational diagnosis, implemented in a participatory manner, and supported by effective internal communication can improve academic performance, administrative efficiency, and foster a collaborative work culture. These findings align with organizational development theory, which emphasizes the importance of systematic and sustainable change. Furthermore, Islamic value perspectives, such as the principles of deliberation, trustworthiness, and responsible leadership, strengthen the ethical foundation for implementing organizational interventions. Thus, planned and values-based organizational intervention projects not only improve managerial effectiveness but also create sustainable and meaningful change for all organizational members.